IMMUNOHYSTOCHEMICAL MARKERS OF ENDOMETRIAL PROLIFERATION ACTIVITY IN PREMENOPAUSAL WOMEN WITH NORMAL MENSTRUAL CYCLE - Gromova, O.L.; Potapov, V.О.; Khaskhachykh, D.A.; Finkova, O.P.; Haponova, О.V.; Kukina, H.О.; Penner, K.V. (World of Medicine and Biology, 2020)
Immunohistochemical markers of proliferative activity, such as p21 and Cyclin D1 genes, E-cadherin, β-catenin, Ki-67 proteins, estradiol and progesterone receptors in the normal endometrium at the proliferative and secretory phase of the menstrual cycle in women have been studied. The dynamics of estradiol and progesterone receptor expression was determined, and it was proved that progesterone receptor expression begins from the first week of the menstrual cycle and is the highest in the glands of the proliferative endometrium. The expression of the Ki-67 proliferation marker is also the highest in the endometrial glands at the proliferation phase and is significantly and reliably reduced in the secretory endometrium. As for the expression of the Cyclin D1 and p21 genes, their feedback was found –at the proliferative phase the expression of the Cyclin D1 gene increased, but p21 was mostly negative, at the secretory phase the activity of Cyclin D1 decreased significantly, and there was a tendency to increase in p21 expression. E-cadherin protein expression increased significantly at the secretory phase of the menstrual cycle, but no significant differences were found in the dynamics of β-catenin expression. The determined parameters of receptor and proliferative activity of the endometrium in healthy premenopausal women can be used as basic information for further study of the endometrial proliferation state in its hyperplastic and neoplastic transformation.
Keywords: endometrium; estradiol receptors; progesterone receptors; p21 gene; Cyclin D1; E-cadherin; β-catenin; Ki-67